2014
DOI: 10.1002/ange.201309539
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Lithium–SO2 Batteries with Ionic Liquids as Electrolytes

Abstract: Li‐SO2 batteries have a high energy density but bear serious safety problems that are associated with pressurized SO2 and flammable solvents in the system. Herein, a novel ambient Li‐SO2 battery was developed through the introduction of ionic liquid (IL) electrolytes with tailored basicities to solvate SO2 by reversible chemical absorption. By tuning the interactions of ILs with SO2, a high energy density and good discharge performance with operating voltages above 2.8 V were obtained. This strategy based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Consequently, the accumulation of inactive and insulating by-products on the pores of the gas electrode would restrict the active reaction sites and the transport of reactants, including lithium ions and SO 2 gas, finally resulting in the cell failures. In previous studies on primary Li-SO 2 batteries, the formation of such by-products has generally been attributed to the self-decomposition of Li 2 S 2 O 4 due to its thermodynamic instability 11 48 60 . According to the XPS analysis of the surface of the cycled cathodes in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the accumulation of inactive and insulating by-products on the pores of the gas electrode would restrict the active reaction sites and the transport of reactants, including lithium ions and SO 2 gas, finally resulting in the cell failures. In previous studies on primary Li-SO 2 batteries, the formation of such by-products has generally been attributed to the self-decomposition of Li 2 S 2 O 4 due to its thermodynamic instability 11 48 60 . According to the XPS analysis of the surface of the cycled cathodes in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The primary Li-SO 2 battery offers a high energy density in a wide operating temperature range with exceptionally long shelf-life and has thus been commercialized for military and aerospace applications since it was developed in the late 1960s (refs 7 , 8 , 9 , 10 ). Recently, the Li-SO 2 chemistry was revisited and proposed as a promising rechargeable battery chemistry 11 12 . Under an analogous cell configuration adopted from lithium-oxygen batteries, it has been demonstrated that a reversible electrochemical reaction between Li and SO 2 is possible with the formation and decomposition of lithium dithionite (Li 2 S 2 O 4 ).…”
mentioning
confidence: 99%
“…Na-SO 2 batteries with high theoretical energy density are attracting more attention as well. Referring to the achievements on Li-SO 2 , [47][48][49] rechargeable Na-SO 2 batteries were first proposed by Kim's group and can be one of the promising candidates for next-generation energy storage systems as well. 50 The research on Na-SO 2 batteries is at the primary stage, focusing on obtaining reversible performance.…”
Section: Sodium-sulfur-dioxide Batteriesmentioning
confidence: 99%
“…Ionic liquid (IL) is regarded as a kind of green solvent with many excellent properties of negligible volatility, nonflammability and high ionic conductivity, and thermal stability [ 11 ]. As reported, ILs can keep stable under high temperatures, not producing significant amounts of volatile products until they reach ~300 °C [ 12 ].…”
Section: Introductionmentioning
confidence: 99%